2020
DOI: 10.3389/fcell.2020.00578
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Cytokines CXCL12, VEGFA, and WNT5A Promote Porcine Oocyte Maturation via MAPK Activation and Canonical WNT Inhibition

Abstract: Maternal regulatory factors endow the oocyte with developmental competence in vivo , which might be absent in current in vitro maturation (IVM) systems, thereby compromising oocyte quality. In the present study, by employing RNA sequencing data analysis, we expect to identify potential contributing factors to support porcine oocyte maturation through binding to their receptors on the oolemma. Here, C-X-C motif chemokine ligand 12 (CXCL12), vascular endothelial grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…Studies in vitro have shown that VEGF supplementation in bovine and pig embryo culture improves cytoplasmatic maturation and blastocyst development rates [ 52 , 53 ]. Recently, Liu et al, (2020) [ 54 ] showed that VEGF improved embryo development rates in vitro, on the one hand, through activation of the MAPK pathway and, on the other hand, via inhibition of the canonical Wnt pathway during the last step of oocyte maturation.…”
Section: Growth Factors and Early Developmentmentioning
confidence: 99%
“…Studies in vitro have shown that VEGF supplementation in bovine and pig embryo culture improves cytoplasmatic maturation and blastocyst development rates [ 52 , 53 ]. Recently, Liu et al, (2020) [ 54 ] showed that VEGF improved embryo development rates in vitro, on the one hand, through activation of the MAPK pathway and, on the other hand, via inhibition of the canonical Wnt pathway during the last step of oocyte maturation.…”
Section: Growth Factors and Early Developmentmentioning
confidence: 99%
“…TZPs are actin-and microtubule-rich structures contacting the oocyte (Albertini and Rider, 1994) through gap junctions (Anderson and Albertini, 1976), and transport essential molecules participating in oocyte maturation (Eppig, 1979;Norris et al, 2009;Macaulay et al, 2016). Furthermore, the number of these structures diminishes throughout oocyte maturation by TZPs retraction (Liu et al, 2020). It has been shown that there is a relationship between TZP integrity and the perivitelline space size (Yuan et al, 2017).…”
Section: General Mechanisms For Polyspermy Blockadementioning
confidence: 99%
“…It has been shown that TZPs are involved in polyspermy blockade since an abnormal TZP retraction allows polyspermy. Liu et al (2020) proposed that the expantion of the perivitelline space is necessary to sever the TZP, close the pores of ZP and prevent sperm penetration on the ZP. Thus, avoiding polyspermy (Liu et al, 2020).…”
Section: General Mechanisms For Polyspermy Blockadementioning
confidence: 99%
See 1 more Smart Citation
“…In specific somatic niches, Wnt5a-Ror2 pathway suppresses canonical Wnt/β-catenin signaling to limit the proliferation of migratory PGCs and promote their movement [17]. Moreover, Wnt5a promotes oocyte maturation and meiotic resumption during postnatal oocyte development [18,19].…”
Section: Introductionmentioning
confidence: 99%